Practical work about anthropology of nursing care - María Teresa Miralles Sangro; Francisca Casas Martínez; Purificación González Villanueva (Universidad de Alicante, 1997)
The present article shows a proposal of methodological work given to students with the aim of preparing their compulsory Practical Work on the Subject: «Anthropology of the Nursing Care», at the Nursing School in the University of Alcalá. The aim of this study is divided in two parts: 1. The student will know the aspects of «nursing care» as a human experience in the different cultures. 2. The characteristics and structures for its implementation and presentation. The results show that a Practical Work prepared by the students of the Subject: «Anthropology of the Nursing Care», furnish them with a global and comparative vision of the day-to-day nursing care, encouraging in them the search of new, more efficient and more adequate ways of helping patients/clients to consider nursing care as a human and universal experience.